Novel approach for a controlled delivery of essential Oils during long-term maize storage: clove bud and pennyroyal oils efficacy to control sitophilus zeamais, reducing grain damage and post-harvest losses - Sousa, Pedro A. S. (2023)
Maize grains represent a significant contribution for assuring food safety all over the globe. Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae), also known as the maize weevil, is one of the most destructive pests in stored maize, causing qualitative and quantitative losses. To control S. zeamais populations in maize storage sites, synthetical chemical insecticides are applied. However, these are often used wastefully, have environmental implications, and can induce the development of resistant populations. In this work, the insecticidal and grain protecting efficacy of an innovative macro-capsule delivery device, loaded with essential oils from Clove bud and Pennyroyal, as well as their combined solutions, was tested against naturally S. zeamais-infested maize grains. The blend of both compounds incorporated in a controlled release device reduced losses by more than 45% over a long storage period of twenty weeks, diminishing the survivability of maize weevils by over 90%. The usage of the blend at a concentration of 370 L L1 air with an antioxidant showed the best results, however, by halving the concentration 185 L L1 air , a significant control of S. zeamais populations was still achieved.